Parental Involvement in the Learning Process During the Covid-19 Pandemic At SDN Remo - Sukma Ayu Kharismawati (Universitas PGRI Adi Buana Surabaya, 2022)
Until now the Corona Virus Disease (Covid-19) pandemic has not completely disappeared from the territory of Indonesia. Its existence has had an impact on social and economic life in the community. The world of education (schools) is one that has been affected and felt by parents and students of the Remo State Elementary School (SDN), Paramasan District, Banjar Regency, South Kalimantan Province. The resulting impact drags the involvement of parents in the child's learning process. Parental involvement occupies an important position when children study at home. Learning at the elementary level formal education (SDN Remo) is carried out offline. Internet network barriers make students at the school follow an offline system or learning that requires face-to-face. Currently, students (students) at SDN Remo study offline. In this learning model, parental involvement occupies an important position. The case study (research) at SDN Remo shows the importance of parental involvement in the learning process during the Covid-19 pandemic. Not only is it important, it also has a big impact when children (students) learn to do the tasks of teachers (educators) at school. The conclusion was drawn from a case study using a descriptive qualitative approach through the instruments of observation, interviews, and documentation.